Research handbook on territorial disputes in international law - Kohen, Marcelo, 1957-; Hébié, Mamadou (Research handbooks in international law, 2018)
Territorial disputes remain a significant source of tension in international relations, representing an important share of interstate cases brought before international tribunals and courts. Analysing the international law applicable to the assessment of territorial claims and the settlement of related disputes, this Research Handbook provides a systematic exposition and in-depth discussions of the relevant key concepts, principles, rules, and techniques. Combining extensive knowledge from across international law, Marcelo Kohen and Mamadou Hébié expertly unite a multinational group of contributors to provide a go-to resource for the settlement of territorial disputes. The different chapters discuss the process through which states establish sovereignty over a territory, and review the different titles of territorial sovereignty, the relation between titles and effectivités, as well as the relevance of state conduct. Select chapters focus on the impact of foundational principles of international law such as the principle of territorial integrity, the right of self-determination and the prohibition of the threat or use of force on territorial disputes. Finally, technical rules that are crucial for the assessment of territorial claims, especially the techniques of intertemporal law and critical date, as well as evidentiary rules, are presented. An essential resource for practitioners, international law academics and public officials including judges and arbitrators, this Research Handbook is a highly original collection of scholarship and research on territorial disputes and their settlement.